Third International Handbook of Mathematics Education - Clements, M.A. (Ken).; Bishop, Alan J.; Keitel, Christine.; Kilpatrick, Jeremy.; Leung, Frederick K.S. (Springer International Handbooks of Education, 2013)
This entirely new Third International Handbook of Mathematics Education comprises 31 chapters which have been written by a total of 84 different authors representing 26 nations, each a recognized expert in the field. Comprised of four sections: Social, Political and Cultural Dimensions in Mathematics Education; Mathematics Education as a Field of Study; Technology in the Mathematics Curriculum; and International Perspectives on Mathematics Education, this Third Handbook offers essential reading for all persons interested in the future of mathematics education. The authors present challenging international perspectives on the history of mathematics education, current issues, and future directions. What makes this Handbook unique is its structure. Each section covers past, present and future aspects of mathematics education. The first chapter in each section identifies and analyzes historical antecedents The <U+001c>middle chapters draw attention to present-day key issues and themes The final chapter in each section reflect on policy matters and future directions We are in an unprecedented era of globalization in education, and this Handbook provides an impressive example of the kind of collaboration needed if we are to make progress on key issues facing mathematics education.